How Does School-Wide Positive Behavior Develop Students’ Positive Behavior? - Arina Mufrihah; Nur Erlinasari (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
This study was aimed to guide students in order to use their smartphone for study needs primarily in classroom learning activities using School-Wide Positive Behavior Support (SWPBS). Classroom Action Research and Spiral Self-Reflective as its design was used as a research method. The research process was conducted in 2 cycles where each cycle comprised planning phase, action phase, and reflection phase. Respondents were selected purposively to be members of group counseling and individual counseling as forms of SWPBS. All data were collected through questionnaire, observation, and interview technique. After receiving counseling services, students have awareness and willingness to not use their smartphone unless it is permitted by teachers for the learning medium or browsing learning resources.